(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2026)
The study aimed to evaluate the implementation of Total Quality Management (TQM) standards in kindergartens in Damascus (public and private), with a sample of 50 public kindergarten teachers and 122 private kindergarten teachers. The results revealed that the overall level of TQM application was moderate, with private kindergartens demonstrating a clear advantage. The most prominent challenge was the absence of a clear strategic plan to enhance quality, which led the researchers to propose a model for improving the application of these standards.